Remarkable enhancement of the electrochemical properties of Co3O4 nanowire arrays by in situ surface derivatization of an amorphous phosphate shell. Issue 4 (3rd January 2019) - Chen, Mingyue; Li, Wenhui; Ma, Wenhao; Qi, Pengcheng; Yang, Wanjun; Wang, Shiyu; Lu, Yu; Tang, Yiwen
Abstract : It is a highly desirable but still a challenging task to find a simple, fast and straightforward method to greatly improve the electrochemical properties of a Co3 O4 electrode for pseudocapacitors. Abstract : It is a highly desirable but still a challenging task to find a simple, fast and straightforward method to greatly improve the electrochemical properties of a Co3 O4 electrode for pseudocapacitors. In this study, we demonstrate that developing an amorphous Co–phosphate (Co–Pi) shell via in situ surface derivatization on a Co3 O4 nanowire (NW) surface facilitates the diffusion and reaction of electrolyte ions and leads to distinctive conductivity. Because of these advantages, 1D nanostructures and the synergistic effect between Co3 O4 and amorphous Co–Pi, the resulting core–shell Co3 O4 @Co–Pi nanowire (NW) array exhibits high capacitance (1692 F g −1 at current density of 1 A g −1 ). In addition, high rate capabilities and retention capacity of 86% after 6000 cycles at 20 A g −1 are achieved. By using the Co3 O4 @Co–Pi core–shell hybrid NW array and activated carbon as the anode and cathode, respectively, asymmetric pseudocapacitors are assembled that exhibit high capacitance (energy density of 35.69 W h kg −1 at power density of 558 W kg −1 ) and super-long cycle life (82% capacitance retention after 40 000 cycles). Our synthesis method provides a new technology for the design of composites of transition metal oxides/hydroxides and phosphates for electrochemical energy storage applications.